Renal Glomerular Mitochondria Function in Salt-Sensitive Hypertension - Domondon, Mark; Polina, Iuliia; Nikiforova, Anna B.; Sultanova, Regina F.; Kruger, Claudia; Vasileva, Valeriia Y.; Fomin, Mikhail V.; Beeson, Gyda C.; Nieminen, Anna-Liisa; Smythe, Nancy; Maldonado, Eduardo N.; Stadler, Krisztian; et al. (Frontiers in Physiology, 2020)
Salt-sensitive (SS) hypertension is accompanied with an early onset of proteinuria, which results from the loss of glomerular podocytes. Here, we hypothesized that glomerular damage in the SS hypertension occurs in part due to mitochondria dysfunction, and we used a unique model of freshly isolated glomeruli to test this hypothesis. In order to mimic SS hypertension, we used Dahl SS rats, an established animal model. Animals were fed a 0.4% NaCl (normal salt, NS) diet or challenged with a high salt (HS) 4% NaCl diet for 21 days to induce an increase in blood pressure (BP). Similar to previous studies, we found that HS diet caused renal hypertrophy, increased BP, glomerulosclerosis, and renal lesions such as fibrosis and protein casts. We did not observe changes in mitochondrial biogenesis in the renal cortex or isolated glomeruli fractions. However, Seahorse assay performed on freshly isolated glomeruli revealed that basal mitochondrial respiration, maximal respiration, and spare respiratory capacity were lower in the HS compared to the NS group. Using confocal imaging and staining for mitochondrial H2O2 using mitoPY1, we detected an intensified response to an acute H2O2 application in the podocytes of the glomeruli isolated from the HS diet fed group. TEM analysis showed that glomerular mitochondria from the HS diet fed group have structural abnormalities (swelling, enlargement, less defined cristae). Therefore, we report that glomerular mitochondria in SS hypertension are functionally and structurally defective, and this impairment could eventually lead to loss of podocytes and proteinuria. Thus, the glomerular–mitochondria axis can be targeted in novel treatment strategies for hypertensive glomerulosclerosis.